The Role of Filter with Different Media Compositions on Water Quality and Survival of Pangasius (Pangasius sp.) in Recirculation Aquaculture System - Ariska Nur Oktavia; Sri Hastuti; Dicky Harwanto (Journal Omni-Akuatika, 2021)
The high market demand for Pangasius (Pangasius sp.) has encouraged farmers to adopt a cultivation system with high stocking densities and high feeding rates. This causes fish farming waste to increase and ammonia in the waters also increases, resulting in a decrease in water quality. One of the efforts to overcome this problem is by using Recirculation Aquaculture System (RAS). This study aims to examine the effect of filters with different media compositions in RAS of Pangasius. Test fish, average weight of 4.59 g, kept for 30 days in aquarium with a density of 1.15 g.L-1. The feed is given at satiation, twice a day. There were five treatments and four replications during study. The treatments were the difference composition of filter media, i.e. A (100% zeolite), B (25% net + 75% zeolite), C (50% net + 50% zeolite), D (75% net + 25% zeolite), and E (100% net). Dacron was used as a mechanical filter in all treatments. The results showed that the composition of different filter materials had a significant effect (P <0.05) on Survival Rate (SR), Total Amount of Feed Fed (TFF), Relative Growth Rate (RGR), and Feed Conversion Efficiency (FCE). The best performance was showed by media biofilter composition of 25% nets + 75% zeolite, with the value of VTR (Volumetric Total Ammonia Nitrogen Removal) were 55.45-66.32 g.m-3.day-1, SR was 93.75%; TFF was 124.84 g; RGR was 2.13%.day-1, and FCE was 46.87%. Various different compositions of net and zeolite as filter media on RAS were able to manage TAN below tolerance limit.Keywords: catfish, recirculation system, filter composition, dacron, net, zeolite.